HUBUNGAN KUALITAS PELAYANAN KEPERAWATAN DENGAN TINGKAT KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS SUNGAI SIRIH KAB. KUANSING TAHUN 2017 - Nany Librianty (Universitas Pahlawan Tuanku Tambusai, 2018)
Increasing the number of patients is one indication of patient satisfaction in health services. At Puskesmas Sungai Sirih the number of patients treated has increased. This study aims to determine the relationship between the quality of nursing service with the level of patient satisfaction inpatient at Puskesmas Sungai Sirih Kab. Kuansing 2017. This type of research is quantitative analytical research with cross sectional study design. The population in this study were inpatients at Puskesmas Sungai Sirih. Samples taken as many as 40 patients by using accidental sampling technique. This research by using questionnaire of quality of service of nursing and questioner of patient satisfaction level so that data obtained is primary data. The analysis used is univariate and bivariate analysis through Chi-square test. Statistical test results obtained P-value value 0.021 <0.05 then it can be concluded there is a relationship between the quality of nursing service with the level of patient satisfaction inpatient at Puskesmas Sungai Sirih Kab. Kuansing in 2017. It is expected that the nurse to improve the quality of nurse's performance in providing better nursing service.